2019
DOI: 10.3389/fnhum.2019.00314
|View full text |Cite
|
Sign up to set email alerts
|

Lasting Effects of Low-Frequency Repetitive Transcranial Magnetic Stimulation in Writer’s Cramp: A Case Report

Abstract: The treatment of writer’s cramp (W’sC) is essentially based on the use of botulinum toxin. However, additional treatments are sometime required to prolong the effects of the toxin, compensate for its progressive loss of efficacy in some subjects, and re-educate handwriting (e.g., rehabilitation strategies). Low-frequency repetitive transcranial magnetic stimulation (rTMS) has been employed to improve W’sC, but with short-lasting and controversial outcomes. We report on the effects of a long-lasting low-frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 66 publications
(126 reference statements)
0
13
0
Order By: Relevance
“…Overall, 19 of the 20 studies reported some reduction in dystonia symptoms after the application of NIBS, however many did not report whether this was statistically significant. Two studies 72, 73 applied rTMS to patients with lower limb dystonia, and one study applied rTMS in a patient with left side multifocal dystonia, which affected the upper and lower limbs 77 .The average number of stimulation sessions was 10 ( SD = 15.1), with a maximum of 75 sessions 69 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 19 of the 20 studies reported some reduction in dystonia symptoms after the application of NIBS, however many did not report whether this was statistically significant. Two studies 72, 73 applied rTMS to patients with lower limb dystonia, and one study applied rTMS in a patient with left side multifocal dystonia, which affected the upper and lower limbs 77 .The average number of stimulation sessions was 10 ( SD = 15.1), with a maximum of 75 sessions 69 .…”
Section: Resultsmentioning
confidence: 99%
“…There was case series in which WC has been improved with the low-frequency repetitive transcranial magnetic stimulation (rTMS), but the results were short-lived and contentious [21]. The effects of a long-term low-frequency rTMS paradigm on WC symptoms are described in a study done in Italy [21]. The study included a 25-year-old man who had been diagnosed with uncomplicated WC [21].…”
Section: Neuromodulation Treatment For Wcsmentioning
confidence: 99%
“…The effects of a long-term low-frequency rTMS paradigm on WC symptoms are described in a study done in Italy [21]. The study included a 25-year-old man who had been diagnosed with uncomplicated WC [21]. The WC Rating Scale (WCRS) and a 1-minute writing test were used to assess him objectively [21].…”
Section: Neuromodulation Treatment For Wcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, antidepressants and muscle relaxants may also be beneficial (Espay et al, 2009 ; Gelauff et al, 2014 ; Ricciardi and Edwards, 2014 ). When these approaches are unsuccessful or not tolerated by the patient, non-invasive brain stimulation has been proposed as a useful add-on to improve a person’s functioning (Nicholson and Voon, 2016 ; Naro et al, 2019a , b ). Specifically, a few studies proposed repetitive TMS (rTMS) as a clinically valuable tool to improve PMDs.…”
Section: Introductionmentioning
confidence: 99%